Bacterial moonlighting proteins of N. meningitidis: interaction with the host and role in pathogenesis - Aljannat, Mahab (2017)
Neisseria meningitidis is a human-restricted pathogen that colonizes the nasopharynx, mostly without causing any disease. However, bacteria can invade into the bloodstream and cross the blood brain barrier resulting in life threatening sepsis and meningitis.